Efl Students’ Writing Apprehension and How It Is Related to Student’s Writing Performance - Pratama, Satria David; Astuti, Utari Praba (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Writing is an active and productive skill, students learning to write in English deal with multiple challenges and difficulties. One of the problem that might be appear on students is writing apprehension. According to several research one of the impact caused by writing apprehension is writing performance. This study examined the level of student’s writing apprehension and the degree of relationship between student’s writing apprehension and writing performance. The Subjects of this research were 38 students in English Education Department. There were two instruments used: Writing Apprehension Test and Writing Test.Abstrak: Menulis merupakan suatu aktivitas yang aktif dan produktif, mahasiswa yang belajar menulis dalam bahasa Inggris akan menghadapi berbagai rintangan dan kesulitan. Salah satu yang akan terjadi adalah kekhawatiran dalam menulis. Menurut beberapa penelitian salah satu dampak yang terjadi karena kekhawatiran tersebut adalah performa menulis seoarang mahasiswa. Penelitian ini menguji tingkat kekhawatiran dalam menulis pada mahasiswa dan tingkat hubungan antara kekhawatiran menulis mahasiswa dan performa. Subjek pada penelitian kali ini adalah 38 mahasiswa jurusan English Education Department. Ada tiga instrumen yang digunakan pada penelitian ini, yaitu Tes Kekhawatiran Menulis, dan Tes Menulis.